Financial Literacy and MSME Sustainability: From Basic Knowledge to Savings, Credit, Investment, and Insurance - Jeandry, Gregorius; Malik, Mahardika Catur Putriwana (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to explore the impact of financial literacy on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Ternate City, focusing on basic knowledge as well as strategies related to savings, credit, investment, and insurance. Employing multiple regression analysis, the study involves a sample of 104 MSMEs selected through purposive sampling from the sectors of food and beverage, fashion, and retail. Descriptive statistics reveal that most MSMEs operate for 6 to 10 years with capital below IDR 50 million and primarily fund themselves through personal funds. Regression results indicate that Basic Financial Literacy and Savings and Credit Literacy have a significant positive impact on MSME sustainability, while Investment and Insurance Literacy do not show significant effects. These findings highlight the importance of enhancing basic financial knowledge and understanding of savings and credit to support MSME sustainability while suggesting the need for more intensive educational programs regarding investment and insurance. The study's limitations include its geographic scope and lack of consideration of external factors, such as macroeconomic conditions, indicating the need for further research with a broader scope and additional variables.